2013
DOI: 10.7567/apex.6.026701
|View full text |Cite
|
Sign up to set email alerts
|

Power Optimization of a Planar Single-Channel Shim Coil for a Permanent Magnet Circuit

Abstract: We propose a new method of designing a power-optimized single-channel shim coil (SCSC), which enables high homogeneity in the magnetic field of a magnetic resonance imaging system. The design method is based on a superposition of multiple circular currents to account for the power dissipated in the current-carrying coils. With a power-optimized SCSC, magnetic field inhomogeneity is largely corrected and there is negligible degradation of the magnetic field in continuous use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The deterioration in homogeneity can be overcome by reducing power dissipation with the combined use of the MCC method, SF method, and power optimization algorithm. Recently we experimentally showed that with a power-optimized SC shim coil, there is negligible heat generation and negligible degradation of the magnetic field in continuous use [45].…”
Section: Discussionmentioning
confidence: 99%
“…The deterioration in homogeneity can be overcome by reducing power dissipation with the combined use of the MCC method, SF method, and power optimization algorithm. Recently we experimentally showed that with a power-optimized SC shim coil, there is negligible heat generation and negligible degradation of the magnetic field in continuous use [45].…”
Section: Discussionmentioning
confidence: 99%
“…14b), for which the puzzle of hardware components is on the road to completion. For example, optical hyperpolarization and NMR detection of 129 Xe have been realized on a microfluidic chip [246]; in pursuit of miniaturizing magnets, concepts for constructing small spectroscopy-grade magnets with homogeneous fields accounting for imperfection of magnet components have been found to be superior to concepts based on perfection of magnet components [247], and shimming by ablation on the atomic scale promises ultimate precision [248], so that residual and temperature-dependent magnetic field inhomogeneities can be reduced by novel concepts of electrical shimming [249,250]. Despite intriguing alternatives such as optical detection [251,252], inductive detection remains the scheme most explored in the context of miniaturization [253][254][255], where tuning to the low resonance frequencies of NMR with permanent magnets is enabled with sacrificial inductances [219], which, when fitted with a high-quality factor, can significantly boost the detection sensitivity [256].…”
Section: Miniaturization and Conclusionmentioning
confidence: 99%
“…6,7) Finally, a designed practical electron gun with a gradual reversal of the magnetic field is used to drive the W-band sixth-harmonic magnetron-type slotted peniotron with a permanent magnet system. 8,9) Extensive efforts are underway to develop a high-frequency, high-efficiency, compact, and short-operational-gap microwave source. The high harmonic slotted peniotron with an axis-encircling electron beam is one approach, due to its advantages in high efficiency and low magnetic field requirements.…”
mentioning
confidence: 99%